Plant-extract-mediated biosynthesis of silver nanoparticles using Eleutherine americana bulb extract and its characterization - JULINDA ROMAULI MANULLANG; RUDY AGUNG NUGROHO; MIFTAKHUR ROHMAH; RUDIANTO RUDIANTO; AMANDA QORYSUCHI (Nusantara Bioscience, 2021)
Abstract. Manullang JR, Nugroho RA, Rohmah M, Rudianto, Qorysuchi A. 2021. Plant-extract-mediated biosynthesis of silver nanoparticles using Eleutherine americana bulb extract and its characterization. Nusantara Bioscience 13: 247-254. The plant-based biosynthesis of nanoparticles has gained increasing momentum due to being lower in cost and eco-friendly. This study aimed to biosynthesize nanoparticles from the ethanolic bulb extract of Eleutherine americana (Aubl.) Merr. Ex K.Heyne (Ea-AgNPs), then characterize Ea-AgNPs and determine their phytochemical content and antioxidant capacity. The Ea-AgNPs were synthesized using ethanolic extract of E. americana bulb along with various concentrations of AgNO3 (0.5-4 mM). The Ea-AgNPs were then characterized using UV-VIS spectroscopic, Scanning Electron Microscopy/ Energy Dispersive X-ray (SEM/EDX), Transmission Electron Microscopy (TEM), X-ray Powder Diffractometry (XRD), and Fourier-Transform Infrared Spectroscopy (FTIR) techniques. The results indicated that E. americana could be used to reduce AgNO3 to synthesize Ea-AgNPs, indicated by color change, and had optimum UV/VIS spectra at 400 nm. The FTIR analysis found that Ea-AgNPs showed peaks at 2919, 2850, 1586, and 1031 cm1, containing several important bio compounds. Additionally, the XRD results found an amorphous Ea-AgNP peak with maximum intensity and proportion of silver occurring at 24 Theta. The particle size distribution curve of Ea-AgNPs showed a size of 105 nm. Furthermore, SEM/EDX analysis revealed an optical absorption characteristic peak at 3 keV. The EDX examination revealed three signals: a strong signal from the C atom (70.99 %), an O atom (28.95 %), and an Ag atom (0.06 %). The TEM imaging also showed the characteristics of Ea-AgNPs. Some phytochemicals such as flavonoids, tannins, alkaloids, and saponins were found in Ea-AgNPs, with IC50 values of 45.30 ppm.